A Role of Intestinal Alkaline Phosphatase 3 (Akp3) in Inorganic Phosphate Homeostasis - Shohei Sasaki; Hiroko Segawa; Ai Hanazaki; Ruri Kirino; Toru Fujii; Kayo Ikuta; Miwa Noguchi; Sumire Sasaki; Megumi Koike; Kazuya Tanifuji; Yuji Shiozaki; Ichiro Kaneko; et al. (Karger Publishers, 2018)
Background/Aims: Hyperphosphatemia is a serious complication of late-stage chronic kidney disease (CKD). Intestinal inorganic phosphate (Pi) handling plays an important role in Pi homeostasis in CKD. We investigated whether intestinal alkaline phosphatase 3 (Akp3), the enzyme that hydrolyzes dietary Pi compounds, is a target for the treatment of hyperphosphatemia in CKD. Methods: We investigated Pi homeostasis in Akp3 knockout mice (Akp3-/-). We also studied the progression of renal failure in an Akp3-/- mouse adenine treated renal failure model. Plasma, fecal, and urinary Pi and Ca concentration were measured with commercially available kit, and plasma fibroblast growth factor 23, parathyroid hormone, and 1,25(OH)2D3 concentration were measured with ELISA. Brush border membrane vesicles were prepared from mouse intestine using the Ca2+ precipitation method and used for Pi transport activity and alkaline phosphatase activity. In vivo intestinal Pi absorption was measured with oral 32P administration. Results: Akp3-/- mice exhibited reduced intestinal type II sodium-dependent Pi transporter (Npt2b) protein levels and Na-dependent Pi co-transport activity. In addition, plasma active vitamin D levels were significantly increased in Akp3-/- mice compared with wild-type animals. In the adenine-induced renal failure model, Akp3 gene deletion suppressed hyperphosphatemia. Conclusion: The present findings indicate that intestinal Akp3 deletion affects Na+-dependent Pi transport in the small intestine. In the adenine-induced renal failure model, Akp3 is predicted to be a factor contributing to suppression of the plasma Pi concentration.